Problematika Layanan Bimbingan dan Konseling di Sekolah - Erda Fitriani; Neviyarni Neviyarni; Mudjiran Mudjiran; Herman Nirwana (Universitas Negeri Padang, 2022)
This article aims to analyze the problems experienced by counselors in carrying out their duties and functions to provide guidance and counseling services in schools. Guidance and counseling are an important component for achieving educational goals. However, in the implementation of services and guidance and counseling experienced various obstacles. In explaining the problem, it is analyzed by the theory of status personality by Raph Linton. The system theory developed by Parson strengthens the analysis to explain the problems in counseling and guidance services in schools. The research was conducted using a qualitative approach through library research or literature study. Based on the research, it was found that the problems experienced in counseling guidance services in schools were the lack of understanding of students, teachers and the community, the professional factor of the counseling teacher and the school management factor and the availability of facilities.